Evaluation of the Tree Composition Suitability in Srengseng Urban Forest DKI Jakarta Province - Aprigianti, Anggi; Susanto, Denni; Mukhlison, Mukhlison (Jurnal Ilmu Kehutanan, 2022)
Urban forest development is one of the efforts in increasing the quantity of green open space while improving water catchment areas and preventing flooding. The selection of the right urban tree species will help optimize the function of the urban forest. The purpose of this study was to evaluating the tree species suitability in the development of Srengseng Urban Forest. Data collection was done through an inventory of all tree species in the urban forest. Literature studies were conducted to analyze the data, by considering the general criteria for urban tree and some specific criteria of tree species for urban forest with conservation purpose. Based on the suitability analyses, each tree species was grouped into three classes of criterion, i.e., appropriate, quite appropriate, and not appropriate. The results showed that among 53 tree species of 23 different families, 90.56% of the tree species were suitable for the development of the Srengseng Urban Forest.